Angelo Filomeno. - Hunt, David; Exhibition. Angelo Filomeno. Claudia Gian Ferrari Arte Contemporanea Milano. 2003-01-21. 2003-03-23 (Milano : Edizioni Charta Milano, 2003)
Born in 1963, Angelo Filomeno moved first to Milan and then to New York. In the theatrical costumer's where he began creating Broadway costumes, thanks to an original means of artistic expression, he succeeded in making the ancient textile tradition into an art appreciated by international critics. Filomeno's world is made up of floral patterns, small leaves, winged insects, stars and drops of blood, which he creates on shantung silk, made especially for him by indian artisans. This book contains the four previously unpublished and poetic seasons of silk thread. Four seasons that no longer exist, reinvented and trapped under the clear Mediterranean sky and between the curves that recall the sinuous shapes of the ancient olive trees of his native land.
bibliog. p. 47
biog. p. 44
ind. tent., gr. tent. lectures p. 45
Engels
Italiaans
boek
Keywords: Filomeno, Angelo